Sedative Effects of Medetomidine and Dexmedetomidine in Cats - Evaluation with Bispectral Index Monitoring (BIS) - Bektaş Bilgiç, Eylem; Demirutku, Alper (Acta Scientiae Veterinariae, 2024)
Background: Sedation is a state of sleepiness and relaxation that results from the depression of the central nervous system. The depth of sedation can be assessed by hemodynamic responses and neurological signs, such as the palpebral reflex, startle response, nystagmus, and response to stimuli. Currently, the Bispectral Index (BIS) is considered the most accurate monitor for assessing brain function during anesthesia and sedation. BIS values for deep sedation between 60-70, and mild to moderate sedation between 70-90. Values above 90 indicate that the patient is awake. This study aims to compare the sedative effects of medetomidine and dexmedetomidine by evaluating the physical examination findings that indicate the depth of sedation, alongside the BIS monitoring, which is an objective monitoring method. Materials, Methods & Results: In this study, 100 cats brought to the Istanbul University-Cerrahpasa Faculty of Veterinary Science, Department of Surgery, Otorhinolaryngology (ENT) Clinic between 2018 and 2022, and indicated for Ventral Bulla Ostectomy (VBO) following examinations, were evaluated for BIS findings and physical examination results after sedation administration. Patients with 1st and 2nd degree anesthesia risk according to the ASA, based on physical, laboratory, and radiological examinations, were included in the study. The 100 patients were randomly divided into 2 groups of 50 each. Following the pre-anesthetic examination, butorphanol (0.4 mg/kg) was administered subcutaneously in both groups preemptively. After 10 min of butorphanol administration, intravenous access through the vena cephalica or vena saphena was obtained using a 22 or 24 gauge angiocath. Medetomidine HCl IV was used for sedation in the 1st group, while Dexmedetomidine HCl (20 μg/kg) IV was used in the 2nd group. After the patients were sedated and complete relaxation was achieved, the self-adhesive sensors of the BIS probe were placed on the frontal region. Posture, jaw tone, palpebral reflex, corneal reflex, pupil size, and limb withdrawal reflex (LWR) were evaluated and recorded before sedation (T0) and at the 5 min following sedation (T1). Discussion: Alpha-2 adrenoceptor agonists can affect both postural and smooth muscles. Relaxation of postural muscles may manifest as recumbency or ataxia. This study's findings were consistent with existing literature: all patients were in lateral recumbency after 5 min following alpha-2 administration, exhibited decreased jaw tone, and allowed their mouths to be opened easily. Moderate sedation in humans is defined as a reversible state in which response to tactile and vocal stimuli is preserved. However, when considering the BIS and LWR findings, we observed that 72% of the moderately sedated patients in the 1st group lost the LWR reflex, which evaluates the response to painful stimuli. This response to painful stimuli, which is more significant than tactile stimuli, partially contradicts the literature. In addition to considering that different sedative drugs may yield different findings, it was believed that the strong muscle relaxant and analgesic properties of medetomidine could explain the results without causing loss of consciousness. In the intergroup evaluation, the mean BIS value of the 1st group was 72.82, indicating moderate sedation. In contrast, the mean BIS value of the 2nd group was 67.12, which was classified as deep sedation. Contrary to the literature, the BIS findings between the groups showed that deeper sedation occurred in the dexmedetomidine group. Based on the BIS findings, we believe that dexmedetomidine will be more effective than medetomidine in procedures requiring procedural sedation by inducing a hypnotic state close to general anesthesia. Keywords: sedative drugs, brain function monitor, BIS findings, LWR (limb withdrawal reflex), sedation, palpebral reflex.